Thermo-chemical conversion kinetics of cannabinoid acids in hemp (Cannabis sativa L.) using pressurized liquid extraction - Urvashi; Joon-Hee Han; Min Hong; Tae-Hyung Kwon; Melvin Druelinger; Sang-Hyuck Park; Chad A. Kinney; Kenneth J. Olejar (BMC, 2024)
Abstract Cannabinoid decarboxylation via thermo-chemical conversion has the potential to reduce the cannabinoid degradation and evaporation due to short reaction time and use of water as the solvent. When combined with pressurized liquid extraction (PLE), thermo-chemical conversion can be performed as the first stage in the extraction procedure. PLE utilizes a closed system at elevated temperatures and pressure to increase the solvation power, which contributes to decreased viscosity and increased diffusion rate. With this new in-extraction decarboxylation approach there remain variables that need full understanding before up scaling from bench top to pilot or commercial scale. Herein, the thermo-chemical decarboxylation kinetics was studied for industrial hemp via PLE at different temperatures (80-160 °C) and reaction times (1-90 min). The reaction was found to be pseudo-first order. Model verification on CBD and CBG resulted in acceptable results; however, an anomaly in the minor cannabinoids suggests that cannabinoid concentration may influence model kinetics.